丹戎布拉大学师范教育学院汉语专业 2019 届学生对动词 “穿”、“戴”与“用”的掌握情况分析 - Felissa Tania; Ina Ina; Bun Yan Khiong (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe three common verbs in Chinese are “chuan”, “dai” and “yong”. They have the same semantics but different specific usages. Therefore, Chinese learners often misuse these three words. In order to understand the mastery condition and analyse the difficulties of students on using the verbs of “chuan”, “dai” and "yong” on the Chinese Language students of Tanjungpura University in academic year 2019, the author used a test method to examine student and analyses the difficulties of “chuan”, “dai” and “yong”. The test results show that the percentage of correct answers for the word “chuan” is 48,42%, the percentage of correct answers for the word “dai” is 57,84% and the percentage of correct answers for the word “yong” is 62,83%. From the results obtained by the author, we can know that they have a better grasp of “yong” and “dai” than “chuan”.Keywords: Verbs, “chuan”, “dai” and “yong”, The Condition of Mastery